Analisis Transparansi, Akuntabilitas Dan Responsibilitas Dalam Pengelolaan Keuangan Dana Desa - Yuli Sartika; Suhar; Faturahman (Trending: Jurnal Manajemen dan Ekonomi, 2023)
One of effect from national development priority agenda in government President Jokowi is issuance of Law No. 6/2014 on Villages, which states that the government will develop Indonesia from the periphery by strengthening regions and villages. The village government is expected to be able to manage it’s territory independently, including the management of assets, finances and village income so that it can improve the quality of life in the village and the welfare of the community. The purpose of this research is to analyze how the implementation, problems and community responses regarding transparency, accountability and responsibility in the management of village funds. This study uses a qualitative descriptive research method. Data collection techniques used are observation, interviews and documentation. The results of this research on how implementation, problems and community responses regarding transparency, accountability and responsibility are quite good, although there are still some obstacles in implementation in the field and the use of responsibilities has not been maximized.